A study of auxiliary factors for judges in sentencing dangerous driving offenses – the mediating role of favorable and unfavorable factors - Liu, Chengjie; Miao, Ziyu; Wang, Ting (Frontiers in Psychology, 2023)
This paper focuses on the study of the ancillary factors considered by judges when sentencing a defendant for dangerous driving offenses. The ancillary factors include favorable and unfavorable ones: the favorable factors, including two indicators, i.e. “Confess” (CF), and “Actively compensate and obtain forgiveness from victims” (AC); unfavorable factors, including two indicators, i.e. “Mainly or solely responsible for the accident” (MSR), and “Behavior on the spot after an accident” (BAA). The study results show that favorable and unfavorable factors mediate the relationship between “Blood Alcohol Concentration” (BAC) and the sentence: there is a significant negative correlation between favorable factors and the sentence and a significant positive correlation between unfavorable factors and the sentence. The favorable factors and the unfavorable factors are both partially mediated between BAC and the sentence. While the mediating effect ratio of the former correlation is 13.8%, the ratio of the latter one is 19.1%. Meanwhile, non-significant differences exist between favorable and unfavorable factors affecting judges’ decisions on imposing a sentence.